PENENTUAN SEKOLAH SEBAGAI TARGET PROMOSI KAMPUS MENGGUNAKAN SIMPLE ADDITIVE WEIGHTING BERBASIS WEB - Riyanto; Fadhilah Oriyasmi; Rien Afrianti (STMIK Catur Sakti Kendari, 2026)
Competition among higher education institutions in Indonesia requires more targeted and data-driven promotional strategies. The Politeknik Negeri Padang (PNP), particularly its off-campus study program in Pelalawan Regency, has traditionally relied on direct school visits, which have not been supported by measurable effectiveness analysis. This study aims to develop a web-based decision support system to determine schools as targets for campus promotion using the Simple Additive Weighting (SAW) method. The criteria used include the distance of schools from the campus, the number of graduates, and the history of applicants, each weighted according to its level of importance. Data collection methods consist of interviews, literature review, and related studies, while the software development follows the waterfall model. The results indicate that the SAW method is capable of producing a systematic ranking of target schools, with SMAN 1 Pangkalan Kerinci achieving the highest rank with a score of 0.74. The implementation of the web-based system shows consistent results with manual calculations, and all system features function properly based on black-box testing.